Uji Daya Hambat serta Penentuan Minimum Inhibitor Concentration (MIC) Dan Minimum Bactericidal Concentration (MBC) Ekstrak Daun Bidara Terhadap Bakteri Patogen - Daris, Ummi Syahda; Syam, Husain; Sukainah, Andi (Agricultural Technology Education Study Program, 2023)
Bidara leaves contain flavonoids, alkaloids, tannins, phenols and saponins which can act as antibacterial by inhibiting the synthesis of microbial cell walls and disrupting the permeability of microbial cell membranes. This study aims to determine the inhibitory power and minimum concentration of bidara leaf extract (Ziziphus spina-christ L) against pathogenic bacteria including Staphylococcus aureus, Bacillus cereus, Salmonella sp. and Escherichia coli. the concentration used in the inhibition test was 100%, while the Minimum Inhibitor Concentration (MIC) and Minimum Bactericidal Concentration (MBC) handling used concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3, 12%, and 1.56% where each test was repeated 3 times. The results obtained from this study were that bidara leaf extract was able to inhibit Staphylococcus aureus, Bacillus cereus and Salmonella sp. with medium inhibition power for bacteria while Eschericia coli has weak inhibition power. Furthermore, in the Minimum Inhibitor Concentration (MIC) treatment, the concentration showing the MIC value for Staphylococcus aureus and Bacillus cerus bacteria was 12.5%, while Salmonella sp. MIC value is shown at 25% concentration. While the Minimum Bactericidal Concentration (MBC) purchase value was not obtained because the bacteria were still growing at a fairly high extract concentration.